Circulating TNF receptors 1 and 2 predict progression of diabetic kidney disease: A meta‐analysis. Issue 8 (24th July 2019) - Ye, Xiaoqi; Luo, Ting; Wang, Kanran; Wang, Yue; Yang, Shumin; Li, Qifu; Hu, Jinbo
Abstract: Background: We conducted a meta‐analysis to investigate the association of circulating tumor necrosis factor‐1 (TNFR‐1) and TNFR‐2 with diabetic kidney disease (DKD) progression, which is the first‐ever quantitative analysis of these associations thus far. Whether TNFRs were better than albumin‐creatinine ratio (ACR) in predicting DKD progression was also explored. Methods: A systematic search of the PubMed, EMBASE, and Cochrane Library databases up to 1 February 2018, was conducted. The main outcome was DKD progression, which was defined as eGFR decline, macroalbuminuria, or incidence of DKD‐related events. Eligible studies were included for pooled analysis using either fixed‐effects or random‐effects models to incorporate between‐study variation by different measurement standards. Publication bias was evaluated using Egger's test. Results: The meta‐analysis included 6526 participants from 11 cohorts with circulating TNFR‐1 measurements and 5385 participants from 10 prospective studies with circulating TNFR‐2 measurements. Compared with the lowest level category, diabetic patients with the highest TNFR‐1 or TNFR‐2 level category exhibited a higher risk of DKD progression (RR 2.51, 95% CI [1.92‐3.27] for TNFR‐1; 3.23 [1.99‐5.26] for TNFR‐2). The risk of DKD progression was also increased with the per unit increment of TNFR‐1 or TNFR‐2 (1.68 [1.43‐1.97] for TNFR‐1; 1.69 [1.31‐2.17] for TNFR‐2). Although existing studies did not support a direct comparison between ACR and TNFRs, it was undeniable that TNFRs could improve the predictive value in DKD progression. Conclusions: Circulating TNFR‐1 and TNFR‐2 are reliable predictors of DKD progression. Whether TNFRs are better than ACR at predicting DKD progression needs to be further investigated.